PENGARUH KUALITAS LAYANAN (SERVICE QUALITY) TERHADAP KEPUASAN MAHASISWA KELAS KARYAWAN FAKULTAS EKONOMI DAN BISNIS, UNIVERSITAS MERCU BUANA - Ryani Dhyan Parashakti; Rini Anggraini; Yusnina Yusnina (Universitas Mercu Buana, 2017)
The research aims to find out the influence of service quality consist of reliability,responsiveness, assurance, emphathy and tangibles on the students’ satisfaction inManagement Deparment of Economic and Business Faculty of Mercu Buana UniversityJakarta. This study is categorized into quantitative research with survey approach. Thetotal sample research are 158 respondents of 2.925 students populations which aredetermined through Solvin formula, while the technique of sampling uses Simple RandomSampling Methode. The research instrument testing uses validity test and reliability test.In the meantime, the data analysis technique uses multiple linear regression withhyphotesis. The results of the research shows that from the calculation of F test, fivedimensions of service quality influences simultanty on the students’ satisfaction inManagement Department of Economic and Business Faculty of Mercu Buana University,Jakarta (Y). From the calculation of t test is proven that partially, variable of tangibles(x1), reliability (x2), responsiveness (x3) and assurance (x4) have a significant influence todependent variable (Y), while the variable of empathy (x5) has no significant influence todependent variable (Y). From the calculation of the coefficient of determination (AdjustedR2) shows a value of 0,999 which means that the influence of the independent variable is99,9%, while the remaining 0,1% is influenced by other variables, beyond the fiveindependent variables.